Preferences over bank and family loans in rural Rwanda - Jörg Peters; Annekathrin Schoofs; Maximiliane Sievert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
We study borrowers' preferences over bank and family loans based on field work undertaken in rural Rwanda. We randomly assigned willingness-to-pay questions for a hypothetical loan offer either by a bank or by a family member to a sample of 480 households. Informal family loans are typically easier to access. Because of the social costs they imply, it is widely believed that family finance is less attractive than formal finance. Our empirical results, however, show no significant difference in preferences over these two choices. This suggests that even if formal credits were widely accessible, people would still also utilize informal finance.
Keywords: D14; O17; 330; informal finance; family loans; bank loans; social collateral; willingness-to-pay